H∞ Filtering for Discrete-Time Stochastic Systems with Nonlinear Sensor and Time-Varying Delay. (19th March 2013) - Hua, Mingang; Cheng, Pei; Fei, Juntao; Zhang, Jianyong; Chen, Junfeng
Abstract : The H ∞ filtering problem for a class of discrete-time stochastic systems with nonlinear sensor and time-varying delay is investigated. By using the Lyapunov stability theory, sufficient conditions are proposed to guarantee the asymptotical stablity with an prescribe H ∞ performance level of the filtering error systems. These conditions are dependent on the lower and upper bounds of the discrete time-varying delays and are obtained in terms of a linear matrix inequality (LMI). Finally, two numerical examples are provided to illustrate the effectiveness of the proposed methods.